Strategi Pelayanan Guru Sekolah Minggu Bagi Pertumbuhan Rohani Anak - Mikha Agus Widiyanto; Nostry Nostry (EDULEAD: Journal of Christian Education and Leadership, 2021)
Sunday school teachers have an important role in the children's spiritual formation. Through the right ministry strategy, children could be guided to grow in their spiritual life. This study aimed to examine the effective Sunday school teacher service strategies in increasing the children's spiritual growth. The method used in this research was correlational. The research was conducted at the Indonesian Gospel Kemah Church, Kombeng District and Telen District, East Kutai District. The results showed that the Sunday school teacher service strategy had a significant effect on children's spiritual growth. Through child-centered learning and teaching creatively the Word of God have an impact on children's spiritual growth and improvement